2019
DOI: 10.1002/jgh3.12203
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of same‐day upper and lower gastrointestinal endoscopy does not affect total procedure' time or medication use: A randomized trial

Abstract: Background and AimSame‐day double upper and lower gastrointestinal endoscopy is frequently performed due to overlapping indications. However, it is unclear whether an upper–lower (U‐L) or lower–upper (L‐U) sequence is optimal. We analyzed the effect of sequence on total procedure time and sedation use.MethodsA total of 100 patients scheduled for same‐day double endoscopy were randomized to the U‐L or L‐U sequence arm. Primary outcomes, mean total procedure time, and sedative dosages were compared using a t‐tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Even though the correlation to the procedure time and sedation time is not dramatically different between the different propofol dosing, the BMI and BSA should be considered as methods of calculating propofol dose, especially in dosing underweight and overweight children, where per kg dosing may be less ideal. Interestingly, one adult study that used propofol found that the UE time was 0.21 minutes longer for every additional BMI unit, which was similar to our study's 0.34 minutes, suggesting that the BMI can potentially be used as a predictor of procedure time [13]. This must be investigated further in prospective studies to consider the viability of creating a standardized dosing regimen for propofol with fentanyl based on BMI or BSA for pediatric UEs, focusing on the safety of that sedation regime.…”
Section: Discussionsupporting
confidence: 84%
“…Even though the correlation to the procedure time and sedation time is not dramatically different between the different propofol dosing, the BMI and BSA should be considered as methods of calculating propofol dose, especially in dosing underweight and overweight children, where per kg dosing may be less ideal. Interestingly, one adult study that used propofol found that the UE time was 0.21 minutes longer for every additional BMI unit, which was similar to our study's 0.34 minutes, suggesting that the BMI can potentially be used as a predictor of procedure time [13]. This must be investigated further in prospective studies to consider the viability of creating a standardized dosing regimen for propofol with fentanyl based on BMI or BSA for pediatric UEs, focusing on the safety of that sedation regime.…”
Section: Discussionsupporting
confidence: 84%
“…While capsule FMT may be considered the safest procedure, our analysis shows a substantially higher primary response to bFMT when compared to treatment with oral capsules [15] . In clinical practice, local availability of these approaches and patient preference will be crucial determinants in the choice of route of application.…”
Section: Article In Pressmentioning
confidence: 67%